Azithromycin (Zithromax®) - James M. McCarty (Hindawi Limited, 1996)
Azithromycin (Zithromax®, Pfizer, Inc., New York, NY) is a 15-membered-ring macrolide and the first azalide antibiotic. It is distinguished from other macrolides by its rapid and extensive penetration into intracellular and interstitial tissue compartments, accompanied by prolonged tissue and serum half-lives. Azithromycin shares the gram-positive activity of erythromycin but is more potent against gram-negative organisms. For urethritis and cervicitis caused by Chlamydia trachomatis, azithromycin is effective and well tolerated in a single dose of 1 g, a regimen recommended by the CDC. A 5-day dosage regimen is available for the treatment of community-acquired respiratory-tract and skin and skin-structure infections caused by susceptible organisms. Azithromycin provides short-duration, high-compliance, cost-effective regimens that should improve outcomes.